Analisis Difusi Inovasi Terhadap Aplikasi Mypertamina - Ulfah Khaidarni; Hairun Nisa; Ahmad Hilal Fauzi; Rangga Galura Gumelar; Ail Muldi (Peneliti.net, 2023)
In the midst of an all-digital and multi-application era, Pertamina released an application in the form of MyPertamina. This is a breakthrough to provide convenience to the public in meeting fuel needs when filling up at gas stations. In addition to facilitating the smooth running of subsidized fuel so that it is right on target. However, in reality, MyPertamina experienced various obstacles. With the theory of innovation diffusion, analyzing various obstacles and finding solutions that can be used. The technology adoption model and the innovation diffusion theory are considered as suitable models to predict user interest in adopting new technology. Dissemination of new ideas or ideas through communication channels is sure to trigger various reactions from the public. In principle, society is not seen as a passive recipient of information, but also as the main participant in development and communication, as local culture and knowledge are valued as part of development.